2D SURFACE RUNOFF MODELLING DUE TO DAM BREAK - WIJAYA - NIM: 25017004, WINDYA
Dam-break incident create a massive and destructive flood. Great losses that occur immediately trigger developing disaster mitigation to minimized losses. The wave propagation that created has unique characteristics such as water level and wave-speed which are important in the planning for early warning systems and flood disaster maps. Mathematical modeling is developed to understand the characteristics of the wave which is water level and wave-speed, also evolution of bed if there any. The developed mathematical model applied finite difference numerical method, that is MacCormack and Lax-Friedrichs schemes to solve the Saint-Venant shallow-water equations without and with sediment transport. The Exner equation is used to model massa conservation and morphological evolution of the bed, while the rate of sediment transport is evaluated with the Meyer-Peter and MÃƒÂ¼ller (MPM) equation. The developed model is written in the programming language (Python within Anaconda Navigator Program). In addition, boundary conditions of Dirichlet and Neumann is applied which are solved by 1D characteristic technique. Numerical filter is used to minimize oscillations along the flow due to high turbulency in dam-break event. The phenomenon of dam-break was modeled as a mass water movement when sudden opening of gate. Calibration phase then conduct with comparing the model results and analytic solutions. In the verification phase, the modeling results are compared with the previous physical model results. The model is tested in many simulations such as flow through a 900 bend, flow through triangle bump, flow with various building configurations, and streams with sand bed. In thsis study, the builfing is modeled as a contour with elevation according to the height of the building. The suitability of the model result with the observation of the physical model indicates that the numerical method used is valid. The numerical flow modeling due to dam-break can be done by the St. Venant equations and produce good flow parameter results using MacCormack and Lax-Friedrichs methods. The presence of obstacles affects the overall flow profile which is the flow energy decreases after crashing the barriers. That resulting in higher upstream water level and the wavefront is move slower to downstream of the channel agaist the unhindered scenario.